Hybrid Contract Analysis on Hajj and Umrah Advance Fund Financing at Tamzis Bina Utama Bandung - Atika Marwah Nasution; Koko Komaruddin; Muhamad Fakhrudin (Mabahits Al-Uqud, 2024)
Hajj and Umrah advance financing is a product created by Islamic financial institutions. Scholars have different opinions regarding the permissibility of using hajj advance financing. That is due to the following: First, regarding the legal validity of hajj and umrah using advance funds, and second, hajj and umrah advance financing uses multiple agreements, namely qardh and ijarah. Third, the impact of hajj advance financing is that the hajj and Umrah waiting lists are increasing. However, many Muslims in Indonesia are interested in this product. Therefore, it is important to implement Sharia principles in the Hajj and Umrah Advance Financing Product so that its implementation does not conflict with Sharia. This study uses an empirical legal approach with a case study method. Data sources consist of primary data obtained through observation and interviews and secondary data sources obtained from documentation and literature studies. The results of this study show that: First, the provisions for hajj and Umrah advance financing may only be given to customers categorized as capable. Second, multiple contracts are carried out separately, and third, the implementation of sharia principles is carried out by referring to MUI Fatwa Number 004/MUNASX/MUI/XI/2020, DSN-MUI Fatwa Number 09 of 2002, and PMA Number 24 of 2016.